The effect of oral contraceptives on orthodontic tooth movement in rat - Olyaee, Pooya (Medicina Oral S.L., 2013)
Introduction: The purpose of this study was to investigate the effect of ethinyl estradiol/norgestrel used in some oral contraceptives- on orthodontic tooth movement in Wistar rats. Material and Methods: Forty eight female three-month old Wistar rats with an average weight of 25025gr were divided into two experimental and control groups. One week prior to appliance insertion and during the appliance therapy period, 100 mcg/kg/day of ethinyl estradiol and 1mg/kg/days of norgestrel were administered to the experimental group by gavage; meanwhile the control group received an equivalent volume of Sodium Chloride 0.9 % (Saline). Maxillary central incisors were tipped distally by insertion of springs exerting 30g force. Two, seven and fourteen days after spring insertion animals were sacrificed. The mesioincisal distance between maxillary incisors were measured. Subsequently, histological sections were prepared for histomorphometric studies. Results: 14 days after force application the orthodontic tooth movement was significantly lower in the experimental group (p<0.05). The number of osteoclasts were significantly lower in the experimental group 2, 7 and 14 days after spring insertion (p<0.05). Conclusion: Ethinyl estradiol/norgestrel (oral contraceptives) can significantly decrease the amount of tooth movement in the linear phase. Key words:Oral contraceptives, orthodontic tooth movement, ethinyl estradiol, norgestrel.